INSTITUTE OF HUMAN RIGHTS OMBUDSMAN - Gүldana Batyrbaevna, Каржасова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
human rights, freedoms, human rights ombudsman, the Ombudsman, the Ombudsman institute.